Tarakan City's Marine Potential As A Teaching Material For Marine Biology: A Systematic Literature Review - Sam, Nur Fitriana; Nursia; Maradhy, Ermawaty; Munira (Universitas Negeri Jakarta, 2024)
This is a Systematic Literature Review (SLR) research that aims to identify the marine potential of Tarakan City which can be used as teaching material in Marine Biology courses. Search using the Publish or Perish 8 application by analyzing articles indexed by Google Scholar and Crossref. After carrying out the process of identification, screening, eligibility, and inclusion, a total of 9 articles were obtained, consisting of 6 Google Scholar articles and 3 Crossref articles. The entire article was analyzed for its suitability with the material content in the marine biology semester learning plan (RPS). Findings of this study show that the marine biota of Tarakan City that can be used as teaching materials for marine biology are seaweed, Signus Jjavus fish, Harpadon nehereus, Ilisha elongate, Protista, and Mangroves Research locations at Amal Beach, Binalatung Beach, Mamburungan, Juata waters, Juata Laut waters, KKMB Tarakan City, and Sadau Island, Indonesia. These articles can be used as teaching material for marine biology regarding the geographical conditions of Indonesian seas, marine animals, marine plants, marine biogeochemical cycles, marine primary productivity, coastal biota, mangrove biota, and research methods for plankton, benthos, and nekton. This research contributes to the planning and preparing of marine biology learning resources based on local potential.